TINGKAT PRODUKTIVITAS DAN PENERAPAN TEKNOLOGI PASCA PANEN KAKAO DI KAMPUNG SIDEY JAYA DISTRIK SIDEY MANOKARI PAPUA BARAT - Nona Maria Intisari Berbander; Ihwan Tjolli; Waromi, Josina (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
The first objective of this research is to determine the productivity of cocoa farming, and the second is to determine the level of application of post-harvest technology in Sidey Jaya Village. The method used in this research is descriptive method with survey approach. The survey sample was 30 respondents who were selected using the purposive method. The results showed that the average cocoa productivity in Sidey Jaya village was 70.22 kg/ha in one harvest. Based on the results of multiple linear analysis, the variables of cost, formal education, farming experience, frequency of attending extension services, number of family members, relative profit and complexity of innovation simultaneously affect the application of cocoa post-harvest technology. However, partially, the variables of formal education and frequency of attending extension services have an effect on the level of application of post-harvest technology. (X1) Formal education has a real effect and (X3) Frequency of attending extension services has a very real effect or can be said to be significant on the level of application of cocoa post-harvest technology (Y). The level of application of post-harvest technology of cocoa farmers in Sidey Jaya Village is low because farmers do not apply all post-harvest technologies.